Analysis of Industrial Worker Housing Location Factors in Malang - Fithri Zainurrohmah; Mufidah; Suko Istijanto Prakasa (Kirana Publisher (KNPub), 2026)
This study examines the determining factors of industrial workers' housing locations as a basis for designing low-cost flats (Rusunawa) in Malang City. The rapid growth of industrial areas has increased the demand for affordable and well-located housing. However, most workers still live in inadequate rental housing with limited environmental quality. This research uses a descriptive qualitative method with spatial analysis through field observation, mapping, and literature review. The results indicate that proximity to workplaces, accessibility, economic affordability, environmental quality, availability of public facilities, and compliance with spatial planning are the main determining factors. Based on site analysis, the selected location at Jl. S. Supriadi XI shows the highest suitability value. This study provides a conceptual basis for planning sustainable and efficient housing for industrial workers.